(untitled) (Physical Culture and Sport: Scientific Perspective, 2025)
Given a number of factors (crisis adolescence, physiological characteristics of the body, the influence of the social environment, the choice of a reference sample for liking, etc.) the adolescent period of personal formation requires significant attention and study. Today, to all those factors that usually cause increased emotional response in adolescence and are associated with being at school: poor academic results/exams, statements by teachers or classmates on this issue, their ridicule, much more intense objective factors have been added that a teenager cannot cope with on their own - life under martial law. The destructive impact on the psyche of Ukrainians of all age categories is associated with the long duration of military operations (more than 3 years) and manifests itself in the form of depression, anxiety disorders, the formation of post-traumatic stress syndrome, reduced working capacity and lack of interest in professional development and growth. The appearance of such negative states, particularly in adolescents, is a very alarming symptom, indicating the need to study this issue more deeply and the urgent need to urgently determine ways to combat such destructive influences. The purpose of this study was to study the experiences and features of the manifestation of the psycho-emotional state of adolescent students in conditions of war in Ukraine. The study showed that in conditions of martial law, most adolescents exhibit instability of their emotional state. Analysis of the results of the projective test showed that for many students, anxiety and uncertainty are now the key emotions due to the awareness of limited control over life. The identified features of psycho-emotional experiences also affect other significant personal properties of adolescent children, in particular, they have a tendency to a low level of aspirations, which may indicate a change in priorities and a lack of faith in a successful and prosperous future while being in conditions of instability and under the influence of stress. The results of the study emphasize the importance of taking into account the emotional state of students in the learning process and the need to create a supportive educational environment.